2003
DOI: 10.1016/s0886-3350(02)01526-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of secondary implantation of flexible open-loop anterior chamber and scleral-fixated posterior chamber intraocular lenses

Abstract: The AC IOLs and PC IOLs were safe and effective for secondary implantation to correct aphakia. Secondary implantation of the scleral-fixated PC IOL seemed to provide a more favorable outcome and a lower complication rate than the open-loop AC IOL in complicated cataract cases with inadequate capsule and zonular support. As scleral-fixated PC IOL implantation is technically more difficult than AC IOL implantation, the decisive factor in choosing a secondary IOL is surgical experience. Long-term comparison of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
0
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 23 publications
8
115
0
10
Order By: Relevance
“…Evereklioglu et al (2003) reported that secondary implantation of the SFIOL will provide more favorable outcome and a lower complication rate than the open-loop ACIOL in complicated cataract cases. In a study by Lee et al (2003) secondary implantation of SFIOL after cataract extraction had a lower early complication rate than primary implantation in complicated cataract extraction although the final visual acuity and late complication rate were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Evereklioglu et al (2003) reported that secondary implantation of the SFIOL will provide more favorable outcome and a lower complication rate than the open-loop ACIOL in complicated cataract cases. In a study by Lee et al (2003) secondary implantation of SFIOL after cataract extraction had a lower early complication rate than primary implantation in complicated cataract extraction although the final visual acuity and late complication rate were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…In patient 2, she had right eye ACIOL implantation. Various studies had compare the outcome of the both technique, both with its own pros and cons (11,12). ACIOL are associated with complication like post-operative corneal decompensation and raised intra-ocular pressure, due to the close contact of the lens with the corneal and angle structures (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques had been described for PSFIOL, including continuous-loop fixation, four points fixation, transcleral fixation through sclerotomy, scleral tunnel technique, etc (13). The complication includes intraocular haemorrhage, retinal detachment, suture erosion and subsequent IOL decenteration (11,12). Some studies have reported higher complications in PSFIOL compare to ACIOL (12).…”
Section: Discussionmentioning
confidence: 99%
“…There have not been many head-to-head studies between techniques to suggest a superior approach, and reviews comparing methods suggests that the effectiveness and safety profiles among the different techniques may be comparable. [24][25][26][27] The approach to addressing these complex surgeries should therefore be evaluated on a case-by-case approach as no one technique may be suitable in all cases. Furthermore,…”
Section: Discussionmentioning
confidence: 99%